Wounded healer: The impact of a grant-supported scholarship on an underrepresented science, technology, engineering, and mathematics student’s career and life - Craig, Cheryl J.; Li, Jing; Rios, Ambyr; Lee, HyeSeung; Verma, Rakesh M. (Frontiers in Education, 2022)
This study narratively untangles an African-American student’s experiences in the throes of receiving a scholarship to study computer science and enter a future STEM career. Using the “wounded healer” metaphor as an interpretative lens, this work explores challenges the young adult experienced relating to his development, culture, contextualized learning, family interactions, religious beliefs, and self-identity. The student’s stories of teaching-learning, transforming and healing instantiate the profound impact the grant-supported scholarship had on the youth’s development, life and career trajectory. Additionally, new connections between narrative and metaphor are forged in ways that strengthen the sense made of teaching-learning, culture, and social interactions in higher education.